PENGARUH EDUKASI PERKEMBANGAN LUKA BERBASIS FOTO TERHADAP KECEMASAN PASIEN ULKUS DIABETIK - Manggasa, Dafrosia Darmi; Rantesigi, Nirva; Nurjayanti, Nurjayanti (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2024)
Diabetic ulcer patients are at risk of anxiety due to changes in health status, wound conditions, fear of amputation, treatment costs and even the threat of death. Anxiety can decrease quality of life as well as hinder wound healing. Education on wound development is important so that patients know the condition and changes in the wound. Research design pre-post test control group design. The sample of 30 diabetic ulcers was divided into two groups, namely the treatment group who received wound development education based on wound photos and the control group who received wound development education without wound photos. Anxiety scores were measured before and after the intervention using the Zung Self-Rating Anxiety Scale questionnaire. The results of the study in the treatment group decreased anxiety scores after the intervention with a mean value of 56.60 and in the control group after the intervention the mean value was 61.47. The results of statistical analysis using the Mann Whitney test obtained a value of p = 0.036. Conclusion that wound development education based on wound photos is effective in reducing anxiety in diabetic ulcer patients. It is recommended for nurses to provide education on wound development accompanied by photos after treatment.